PENGARUH KORUPSI DAN UTANG LUAR NEGERI TERHADAP KEMISKINAN DI INDONESIA TAHUN 2003-2022 - Mahardhika Harilinawan; Arga Christian Sitohang (widya balina, 2025)
This study aims to determine the effect of corruption and external debt on poverty in Indonesia during the period 2003–2022, both simultaneously and partially. The data used in this study are secondary data obtained from the World Bank (WB) and Transparency International (TI). The analysis was conducted using the multiple linear regression method with the assistance of EViews 13 software. The results show that, simultaneously, corruption and external debt variables influence the level of poverty in Indonesia. Partially, both variables have a negative and significant effect on poverty during the study period. This means that the lower the level of corruption and the better the management of external debt, the lower the poverty rate in Indonesia tends to be. Overall, the findings indicate that reducing the level of corruption and improving external debt management are important steps in poverty alleviation efforts in Indonesia.